Tinjauan Yuridis Terhadap Notaris Yang Dinyatakan Pailit Ditinjau Berdasarkan Undang-Undang Jabatan Notaris - Aga Waskitha Wiryawan (Lex Renaissance, 2020)
This research discusses the Juridical Review of Notaries who have been Declared as Bankrupt under the Law of Notary Office. The problems formulated in this study are 1) What are the factors to declare a Notary as bankrupt based on the Law on Notary Office? 2) What is the legal consequence of a Notary declared bankrupt based on the Law on Notary Office? This is a normative study with statutory approach and qualitative analysis methods. The results of this research conclude that the factors to declare a Notary as bankrupt by the court, among others, due to the inability to pay compensation to creditors outside of his / her position as a notary, namely as someone with another business that does not violate his / her position. Furthermore, the legal consequence of the bankruptcy is being dishonorably discharged by the Ministry of Law and Human Rights, which violates the dignity of the Notary in accordance with the rules in the Notary Code of Ethics, hence it is considered a disgraceful act and humiliates the Notary's dignity and position.